ChemInform Abstract: Photochemical Route for Accessing Amorphous Metal Oxide Materials for Water Oxidation Catalysis. Issue 31 (11th July 2013) - Smith, Rodney D. L.; Prevot, Mathieu S.; Fagan, Randal D.; Zhang, Zhipan; Sedach, Pavel A.; Siu, Man Kit Jack; Trudel, Simon; Berlinguette, Curtis P.
Abstract Photochemical metal‐organic deposition produces amorphous (mixed) metal oxide films, which show high electrocatalytic activity for the oxygen evolution reaction.